The myth of mob rule: violent crime and democratic politics - Miller, Lisa Lynn (Oxford University Press, 2016)
Mass publics, crime, and democratic politics -- Security from violence as collective good -- The non-politics of crime in post-war Britain -- Violence, racialized risk, and U.S. exceptionalism -- Collective security in the Netherlands -- Two cheers for mob rule